2003
DOI: 10.1089/109493103322725342
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Wrong Buttons: Men's and Women's Attitudes toward Online and Offline Infidelity

Abstract: Pushing the wrong buttons 2 2 ABSTRACT Despite current researchers' interest in the study of online sexual addiction, there is a dearth of research available on what constitutes online infidelity. This paper attempts to redress this balance by comparing 1117 participants' attitudes toward online and offline acts of infidelity. A factor analysis was carried out which yielded three components of infidelity: sexual infidelity, emotional infidelity and pornography.More importantly, this study revealed that online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
120
2
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 25 publications
(20 reference statements)
10
120
2
14
Order By: Relevance
“…Parker and Wampler's (2003) study, which considered sexual online activities, found that women viewed these activities more seriously than men did. Whitty's (2003a) study further found that overall women were more likely than men to believe that online sexual acts were an act of betrayal. In this current study we were also interested in examining what types of online behaviors men and women considered to be inappropriate.…”
Section: Netiquette Within Married Couplesmentioning
confidence: 81%
See 4 more Smart Citations
“…Parker and Wampler's (2003) study, which considered sexual online activities, found that women viewed these activities more seriously than men did. Whitty's (2003a) study further found that overall women were more likely than men to believe that online sexual acts were an act of betrayal. In this current study we were also interested in examining what types of online behaviors men and women considered to be inappropriate.…”
Section: Netiquette Within Married Couplesmentioning
confidence: 81%
“…Previous research found that individuals typically regard online acts of infidelity as significant as offline acts of infidelity (Mileham, 2007;Parker & Wampler, 2003;Whitty 2003aWhitty , 2005Whitty & Quigley, in press). Hence, it makes sense that in the majority of couples in our study both partners said that they would be unhappy if their partner was engaging in such activities online.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations